2012
DOI: 10.3354/ame01589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different salinities on growth and intra- and extracellular toxicity of four strains of the haptophyte Prymnesium parvum

Abstract: The present study investigates the effect of brackish (7 PSU) and marine (26 PSU) salinity on physiological parameters and intra-and extracellular toxicity in 4 strains of Prymnesium parvum Carter. The different P. parvum strains were grown in batch cultures in 2 trials under different experimental conditions to test the development of intra-and extracellular toxicity during growth. The response of P. parvum toxicity to salinity was validated using 2 protocols. Intraspecific variations in growth rate, maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For example, these effects have been recently investigated in four P. parvum strains using an erythrolytic assay for measuring endotoxin levels and a cryptophyte (Rhodomonas salina) bioassay for exotoxin assessment (Weissbach and Legrand, 2012). Although they achieved lower cell concentrations compared with what we routinely obtained, their study similarly reported the highest toxicity of extracellular toxins at brackish salinity levels (7 PSU in their case).…”
Section: Discussionmentioning
confidence: 72%
“…For example, these effects have been recently investigated in four P. parvum strains using an erythrolytic assay for measuring endotoxin levels and a cryptophyte (Rhodomonas salina) bioassay for exotoxin assessment (Weissbach and Legrand, 2012). Although they achieved lower cell concentrations compared with what we routinely obtained, their study similarly reported the highest toxicity of extracellular toxins at brackish salinity levels (7 PSU in their case).…”
Section: Discussionmentioning
confidence: 72%
“…It has been suggested that up to 78% of the cellular nitrogen and 45% of the cellular phosphorus may be acquired via predation (Carvalho and Granéli, 2010 ). The heterotrophic capabilities of the alga include the production of a suite of toxins that exhibit hemolytic, ichthyotoxic, cytolytic, and potentially neurotoxic activities (Edvardsen and Paasche, 1998 ; Barkoh and Fries, 2010 ; Henrikson et al, 2010 ; Bertin et al, 2012 ; Granéli et al, 2012 ), and toxin characterization is an area of active research (Schug et al, 2010 ; Weissbach and Legrand, 2012 ; Manning and La Claire, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The haptophyte Prymnesium parvum was found to increase allelopathy under low-salinity conditions. 52 Extracts of P. parvum grown at high and low salinities were tested for hemolytic activity as a proxy for intracellular biological activity. Filtrates from P. parvum cultures grown at high and low salinities were tested for allelopathy against the cryptophyte Rhodomonas salina as a proxy for extracellular toxin content.…”
Section: Role Of Allelopathy In Altering Species Composition Of Commu...mentioning
confidence: 99%